What is the avifauna of Amazonian white-sand vegetation?. Issue 2 (28th September 2015) - BORGES, SÉRGIO HENRIQUE; CORNELIUS, CINTIA; RIBAS, CAMILA; ALMEIDA, RICARDO; GUILHERME, EDSON; ALEIXO, ALEXANDRE; DANTAS, SIDNEI; SANTOS, MARCOS PÉRSIO DOS; MOREIRA, MARCELO
Summary: White-sand vegetation (WSV) is a rare vegetation type in the Amazon basin that grows in nutrient impoverished sandy soils that occur as patches of variable size. Associated with this vegetation is bird assemblage that has not yet been fully characterized. Based on published species inventories and our own field data we compile a checklist of bird species recorded in WSV. In addition, we compared the avifauna of WSV with that found in savanna patches, another type of Amazonian open vegetation. WSV hosted a distinctive avifauna including endemic and threatened species. The number of bird species was lower in WSV compared to nearby terra firme forests, seasonally flooded forests and Amazonian savannas. Despite its low diversity, the avifauna of WSV has a distinctive species composition and makes a significant contribution to Amazonian beta diversity. At least 35 bird species can be considered as indicator species for this environment. Previously identified areas of endemism within the Amazon basin house at least one WSV indicator bird including cases of congeneric species with allopatric distributions. Seven of the WSV indicator species (20% of this avifauna) are in an IUCN threatened category, with one species Polioptila clementsi considered Critically Endangered. Their isolated distribution, small area occupied, and fragility to human-driven disturbances makes WSV one of the most threatened vegetation types in the Amazon basin. The study of WSV avifauna contributes to a better understanding of mechanisms that generate and maintain species diversity as well as of the environmental history of the most biologically diverse biome of the planet.